Analisis Sistem Sapaan Kekerabatan pada Masyarakat Dayak Kerabat di Kabupaten Sekadau - Herlina Herlina; Fitri Wulansari; Abang Ismail Bin Haji Abang (Jurnal Pendidikan Bahasa, 2025)
The Dayak Kerabat community in Sekadau Regency has a kinship address system that not only reflects biological relationships but also embodies social norms, customs, and cultural values that are highly esteemed. This study aims to analyze the forms and meanings of kinship address terms in the Dayak Kerabat community and to understand how this system plays a role in building and maintaining social relationships. This research employs a descriptive method with a qualitative approach in sociolinguistics. Data were obtained through interviews with selected informants. The data analysis technique follows Miles and Huberman’s interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the kinship address system in the Dayak Kerabat community is divided into two main lineage patterns: vertical and horizontal. The terms of address used not only signify blood relations but also carry social meanings, such as respect for elders, social stratification, and customary marriage regulations. This study contributes to sociolinguistic research and the preservation of local language and culture, particularly in understanding the social dynamics of the Dayak Kerabat community.